Thermodynamic comparison of direct supercritical CO2 and indirect brine-ORC concepts for geothermal combined heat and power generation. (December 2020) - Schifflechner, Christopher; Dawo, Fabian; Eyerer, Sebastian; Wieland, Christoph; Spliethoff, Hartmut
Abstract: Petrothermal reservoirs contain a tremendous technical potential without major regional restrictions. The application of supercritical CO2 (sCO2 ) as a heat carrier might be a promising alternative to the commonly discussed usage of water. This study evaluates both heat carriers for a CHP application. A novel CHP plant layout for a thermosiphon with direct utilization of sCO2 for power generation and a pumped brine system with a parallel CHP plant and power generation by an Organic Rankine Cycle (ORC) are compared for a defined mass flow rate of 225 kg/s and reservoir conditions of 180 °C and 49 MPa. For the ORC with R245fa the annual amount of net electricity is 3% higher than for the ORC with R1233zd(E) and 8% higher than for the sCO2 case. The net power of the sCO2 plant displays a significantly higher sensitivity to changes of the heat demand compared to the brine-ORC system. While the average exergetic efficiency for the brine concept is 40.9% for R245fa and 40.0% for R1233zd(E), respectively, the sCO2 concept reaches an average efficiency of 72.6%. Finally, two different operation strategies for the sCO2 CHP plant are investigated against the background of potential turbine part-load models. Graphical abstract: Image 1 Highlights: Petrothermal resources have a tremendous potential for heat and power generation. Supercritical sCO2 and water are compared as potential heat carriers. sCO2 displays a higher sensitivity to varying heat demand. The selected turbine-part load model has an significant impact.